Utilization of Electronic Learning Media to Support the Professionalism of Islamic Religious Education Teachers at SMP Negeri 1 Babat - Agung Novianto; Eka Amalia Ernanda; Rizka Ananda Puspita Sari; Ahmad Mahfudho Yurokhim (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
The advancement of electronics has grown and permeated various fields, including education. Electronic media can facilitate teachers in carrying out their profession, particularly in the case of Islamic Education teachers (PAI). Moreover, PAI lessons are considered tedious by a significant portion of school students. Most teachers rely solely on lecturing methods during the teaching process. One way to address this issue is by harnessing electronic learning media during the instructional process, especially for challenging topics students find difficult to grasp. This approach aims to spark students' interest in the subject matter. The objectives of this research are as follows: (1) to understand the perception of Islamic Education teachers regarding the benefits of electronic learning media, (2) to determine the utilization of electronic learning media at SMP Negeri 1 Babat (a public junior high school), and (3) to identify the supporting factors for the utilization of electronic learning media at SMP Negeri 1 Babat. The research employs a qualitative approach with a descriptive research design. Data collection techniques encompass interviews, observations, and documentation. The gathered data are analyzed through data reduction, presentation, and conclusion. The outcomes of this study reveal that: (1) All Islamic Education teachers comprehend the benefits of electronic learning media. (2) Among the four Islamic Education teachers at SMP Negeri 1 Babat, one teacher struggles to employ electronic learning media due to skill limitations. (3) The supportive factors for the utilization of electronic learning media at SMP Negeri 1 Babat include teachers' abilities, facilities and infrastructure, student readiness, and support from the school administration.